DISCURSIVE ARCHITECTURES OF POWER: REVISITING TEUN A. VAN DIJK’S TRIADIC MODEL OF DISCOURSE, COGNITION, SOCIETY IN POSTCOLONIAL SOUTH ASIA FROM COLONIAL PAST TO DIGITAL PRESENT (Contemporary Journal of Social Science Review, 2025)
Teun A. van Dijk’s Elite Discourse and Racism (1993) revolutionized the study of ideology by framing racism as a linguistic, cognitive, and institutional system rather than a biological or emotional bias. This article revisits Van Dijk’s Triadic Model of Discourse–Cognition–Society across the historical continuum of South Asia touching the colonial past to the digital present, to trace how linguistic and ideological hierarchies evolve yet persist through discourse. Using a Critical Discourse Analysis (CDA) approach, this study connects colonial-era newspapers (The Times of India, The Civil and Military Gazette, The Statesman) with contemporary South Asian media, policies, and digital communication (2023–2025).The analysis demonstrates that discursive racism has transitioned from overt imperial rhetoric to symbolic and moralized language. In colonial times, English-language newspapers framed domination as “civilization”; in postcolonial South Asia, nationalist and bureaucratic discourses reproduce exclusion under slogans like “unity,” “integration,” or “merit.” In the digital present, hashtags, tweets, and political speeches continue to naturalize linguistic hierarchies through the moral grammar of patriotism.By integrating Van Dijk’s Triadic Model with postcolonial and decolonial theory, the paper argues that modern racism in South Asia is not about color but about control of meaning, the power to define belonging and legitimacy through discourse. It concludes that decolonizing communication systems, curricula, and digital platforms is essential to disrupt the recursive cycle of linguistic domination that connects empire to modernity.